Time from diagnosis to treatment has no impact on survival in newly diagnosed acute myeloid leukemia treated with venetoclax-based regimens - David Baden; Sven Zukunft; Gema Hernandez; Nadine Wolgast; Sophie Steinhauser; Alexander Pohlmann; Christoph Schliemann; Jan-Henrik Mikesch; Bjorn Steffen; Tim Sauer; Maher Hanoun; Kerstin Schafer-Eckart; et al. (Haematologica, 2024)
In newly diagnosed acute myeloid leukemia, immediate initiation of treatment is standard of care. However, deferral of antileukemic therapy may be indicated to assess comorbidities or pre-therapeutic risk factors. We explored the impact of time from diagnosis to treatment on outcomes in newly diagnosed acute myeloid leukemia undergoing venetoclax-based therapy in two distinct cohorts.